Contrast-enhanced ultrasound reveals superior gluteus medius muscle vitality after total hip arthroplasty in a minimally invasive anterolateral versus lateral surgical approach - Mick, Paul; Schaible, Robin; Renkawitz, Tobias; Walker, Tilman; Innmann, Moritz Maximilian; Tsitlakidis, Stefanos; Hariri, Mustafa; Doll, Julian (Ultrasound in medicine & biology, 2024)
Objective - Total hip arthroplasty (THA) is essential for treating severe osteoarthritis. With various surgical approaches available, there has been a shift toward techniques that offer quicker recovery and fewer complications. In this study, contrast-enhanced ultrasound was used to evaluate the impact of the minimally invasive anterolateral versus conventional lateral approach in THA on the gluteus medius muscle, focusing on muscle vitality and functional outcomes. - Methods - A retrospective, cross-sectional analysis of 64 patients who underwent unilateral THA (26 lateral and 38 anterolateral) was conducted. Muscle strength was measured alongside joint flexibility and patient-reported outcome measures. Contrast-enhanced ultrasound (CEUS) examinations were conducted to visualize gluteus medius microperfusion. CEUS data were analyzed using VueBox 7.1 software and microperfusion parameters were calculated using peak enhancement (PE), wash-in perfusion index (WiPI) and rise time for muscle vitality evaluation. - Results - Patients from the anterolateral group exhibited higher relative muscle strength in the operated hip compared with the healthy side (96 ± 23% vs. 86 ± 23%, p = 0.048). CEUS revealed superior gluteus medius microperfusion in the anterolateral group (PE 36,300 ± 42,000 arbitrary units [a.u.] vs. 20,400 ± 20,200 a.u., p = 0.024; WiPI 23,600 ± 27,300 a.u. vs. 13,500 ± 13,300 a.u., p = 0.027). A positive Trendelenburg sign was evident in 2 out of 26 patients in the lateral group compared with none in the anterolateral group (χ2 = 0.082), indicating higher rates of gluteal insufficiency in the lateral approach group. - Conclusion - Significantly higher muscle perfusion parameters in the anterolateral group, alongside improved muscle strength recovery, hint at a subtle but important advantage regarding post-operative recovery of the anterolateral approach. These findings support the ongoing trend toward minimally invasive surgical approaches in THA.
Gesehen am 26.02.2025